DETERMINATION OF DEPENDENCE OF CHEWELESS EFFECTS FROM TEMPERAMENT - K.D. Toncheva; D.M. Korol; I.V. Zaporozhchenko; D.V. Kalashnikov; D.D. Kindii (Ukrainian Medical Stomatological Academy, 2018)
Introduction. Studies have shown that the style of each person's activity largely depends on the type of higher nervous activity entering the structure of his temperament. The temperament of an individual is considered innate, because it is a psychic property that does not lend itself to pedagogical correction and volitional regulation. Since the type of temperament affects the overall activity of the person, the idea arose to investigate the possibility of its influence on the work of the maxillofacial apparatus of young, healthy people. The aim of the work is to analyze the degree of dependence between chewing efficiency and human temperament with the help of the proposed improved method of chewing sampling. Materials and methods. The study, in which 59 people took part, of them 27 men (45.8%) and 32 women (54.2%) aged 17-25 years, was conducted on the basis of the laboratory of the Department of Propaedeutics of Orthopedic Dentistry of the HSEEU "Ukrainian Medical Stomatological Academy "(Poltava). The analysis of the obtained data showed absolute numerical superiority among the surveyed representatives of two temperamental groups: 1 group - sanguine, 17 of them 10 men and 7 women; 2 group - choleric people, 24 of them 9 men and 15 women. Samples for the chewing test were colloidal mass of agar-agar in the form of cylinders with a height of 10 and a diameter of 20 millimeters. All participants did 10 conventional chewing movements to grind the samples, after which all fragments of the test material were collected, washed, dried, the information was converted into photograph and was recorded in a computer base. Results. In the sanguine group, in determining the masticatory efficiency, the total number of fragments of the test sample ranged from 140.6 to 471.3, the average area of the fragments was 91.727 - 345.175 pxl2. In the choleric group, the total number of fragments of the test sample ranged from 194 to 644, and the average size of the fragments in the choleric group fluctuated 75.15 - 191.101 pxl2. The results of the study showed that representatives of the choleric group had a large total number of fragments of the test sample and a smaller average area. An increase in the number of fragments and a decrease in their area indicate a high masticatory efficiency, and therefore a better quality of chewing food, is observed in the choleric group. In the sanguine group, there is less total number of fragments and a larger average area compared to choleric, which indicates a lower chewing efficiency and, correspondingly, worse processing of food. Hypothesis (M0) on the absence of a statistical relationship between the parameters of the chewing test and a certain type of human temperament was developed. Accordingly, the alternative hypothesis (M1) relied on the assumption of a statistical relationship between these indicators. The obtained results did not allow rejecting the null hypothesis as when comparing the values of the total number of fragments and the mean values of these fragments. But, the confidence interval (0.052) of the mean fragment area values approaches the accepted critical level of significance (p = 0.05). Conclusions. Further statistical analysis showed that the numerical index of the average area of the chewing gum fragments is more reliable to a certain type of temperament in the experienced persons, which makes it possible to consider this parameter as a sensitive marker for assessing the condition of the dentoalveolar system in normal and pathological changes, including when determining the effectiveness of the orthopedic treatment.